2015
DOI: 10.1186/s12885-015-1037-z
|View full text |Cite
|
Sign up to set email alerts
|

High levels of dietary soy decrease mammary tumor latency and increase incidence in MTB-IGFIR transgenic mice

Abstract: BackgroundEpidemiologic data indicates that Asian diets, which are high in soy protein, reduce a women’s risk of developing breast cancer. However, it has been difficult to dissociate the benefits of soy from other variables including environmental and lifestyle factors. Since prospective studies in humans would take decades to complete, rodent models provide a valuable research alternative.MethodsIn this study, MTB-IGFIR transgenic mice, which develop mammary tumors resulting from overexpression of the type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Primer efficiencies were as follows, Spp1 – 104, Itgav – 101, Itgb3 – 99, Cd44 – 101, Hprt – 105, and Ywhaz – 110. The expression of Spp1, Itgav, Itgb3 and Cd44 were determined relative to the house-keeping genes Hprt and Ywhaz which were previously been shown to be suitable from a panel of 14 potential housekeeping genes [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Primer efficiencies were as follows, Spp1 – 104, Itgav – 101, Itgb3 – 99, Cd44 – 101, Hprt – 105, and Ywhaz – 110. The expression of Spp1, Itgav, Itgb3 and Cd44 were determined relative to the house-keeping genes Hprt and Ywhaz which were previously been shown to be suitable from a panel of 14 potential housekeeping genes [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…[100] Soy containing various concentrations of isoflavones when fed at high levels to MTB-IGFIR transgenic mice (mice developing mammary tumours by the over expression of type I insulin-like growth factor receptor) promoted the development of mammary tumors which appears to be associated with increased expression of Areg (marker of ER signaling). [101] A meta-analysis study by Hamilton-Reeves et al, [102] suggested that neither soy foods nor its isoflavones have any significant impact on the reproductive hormone (testosterone) levels in men with the risk of prostate cancer (PC). A 6month intervention of mixed SI had no effect in reducing breast epithelial proliferation in healthy, high risk adult western women (n = 126).…”
mentioning
confidence: 99%
“…In addition to the transgenic mice describe above, MTB-IGFIR transgenic mice [65] have also been used to investigate soy isoflavone’s impact on mammary tumorigenesis [66]. MTB-IGFIR transgenic mice overexpress the human insulin-like growth factor receptor (IGF-IR) in mammary epithelial cells in a doxycycline-inducible manner [65].…”
Section: Rodent Mammary Tumor Modelsmentioning
confidence: 99%
“…Meanwhile, the other study found no impact on tumor incidence in MMTV- neu transgenic mice fed a high soy diet compared to controls [95]. In the study using MTB-IGFIR mice, tumor incidence was increased and tumor latency was decreased in MTB-IGFIR mice fed a diet containing 20% ISP compared to casein-fed MTB-IGFIR mice [66].…”
Section: Mammary Tumor Development Following Lifetime Soy Isoflavomentioning
confidence: 99%